2002
DOI: 10.1161/01.cir.0000018751.52074.e9
|View full text |Cite
|
Sign up to set email alerts
|

Giant Left Atrium Associated With Mitral Valve Prolapse

Abstract: I thoroughly enjoyed Hurst's dissertation on the etiology of a giant left atrium 1 and concurred that a giant left atrium seldom results from severe mitral regurgitation due to a nonrheumatic cause such as mitral valve prolapse. Although I would never dare to challenge Dr Hurst on anything he said or wrote, because I consider him not only as the master clinician of the century but also as my mentor, I thought it might be of interest to point out that there were 2 cases reported in the literature of a giant lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 5 publications
1
4
0
1
Order By: Relevance
“…All patients were more than 50 years old, with the medium age in the 7th decade, which fits the theory that most of the subtle anatomic changes present in the cases with right-to-left shunt are age-related, which could explain the late onset of symptoms [22]. Aging may affect the size of the PFO as it is related to aortic root dilation, kyphoscoliosis, distortion of the interatrial septum or stiffness of the right ventricle.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…All patients were more than 50 years old, with the medium age in the 7th decade, which fits the theory that most of the subtle anatomic changes present in the cases with right-to-left shunt are age-related, which could explain the late onset of symptoms [22]. Aging may affect the size of the PFO as it is related to aortic root dilation, kyphoscoliosis, distortion of the interatrial septum or stiffness of the right ventricle.…”
Section: Resultssupporting
confidence: 62%
“…As Cheng [22] has stated, we believe that, besides the structural component provided by the existence of an interatrial communication, a functional premise also has to be present to cause this inverted direction of flow with orthostatism.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the presence of only these anatomical factors cannot induce POS because they usually cause left-to-right shunting. In addition, functional factors, such as right hemidiaphragmatic paralysis, pericardial effusion, constrictive pericarditis, emphysema, arteriovenous malformation, pneumonectomy, liver cirrhosis, aortic aneurysm, or elongation changes of shunt flow can determine POS [7]. Many previous reports indicated that POS can occur for various reasons.…”
Section: Discussionmentioning
confidence: 99%
“…However, its rarity in the current era is particularly due to the decreased incidence of rheumatic fever. A giant LA of non-rheumatic origin is, instead, extremely unusual when caused by severe mitral regurgitation accompanying mitral valve prolapse [4]. However, a giant LA of non-rheumatic origin is a rare entity because it is not presumably associated with primary disease of the left atrial myocardium, in which the remodeling of the musculature is implicated in the face of rheumatic heart disease and with a higher incidence in mitral valve disease.…”
mentioning
confidence: 99%